Hubungan Self Esteem dengan Keaktifan Belajar IPS Siswa Kelas V SDN Kelurahan Tebet Timur Jakarta Selatan - Resti Larasati; Mohamad Syarif Sumantri; Taofik (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Self-esteem is an individual’s assessment of themselves that can influence students’ behavior and engagement in the learning process. This study aims to determine the relationship between self-esteem and social studies learning engagement among fifth-grade students at an elementary school in Tebet Timur, South Jakarta. This study employed a quantitative method with a correlational design. The sample consisted of 126 students selected using proportional random sampling. Data were collected through self-esteem questionnaires and social studies learning engagement questionnaires, then analyzed using the Pearson Product-Moment correlation test after conducting prerequisite tests, namely the normality test and the linearity test. The results showed a positive and significant relationship between self-esteem and social studies learning engagement, with a correlation coefficient of r = 0.678 and a significance level of p < 0.001. This means that the higher a student’s self-esteem, the higher their social studies learning engagement, with a contribution of 46% based on the coefficient of determination. The results of this study indicate that self-esteem is one of the psychological factors that play a role in encouraging students’ active participation in learning. Students with high self-esteem tend to be more confident and willing to actively participate by asking questions, answering questions, engaging in discussions, and expressing their opinions during the social studies learning process